Antineoplastic Effect of Lenvatinib and Vandetanib in Primary Anaplastic Thyroid Cancer Cells Obtained From Biopsy or Fine Needle Aspiration - Ferrari, Silvia Martina; La Motta, Concettina; Elia, Giusy; Ragusa, Francesca; Ruffilli, Ilaria; Quattrini, Luca; Paparo, Sabrina Rosaria; Piaggi, Simona; Patrizio, Armando; Ulisse, Salvatore; Baldini, Enke; Materazzi, Gabriele; et al. (Frontiers in Endocrinology, 2018)
Anaplastic thyroid carcinoma (ATC) is a malignant tumor of the thyroid gland, infrequent but with a very poor prognosis, as it rapidly causes death (mean survival of about 6 months). ATC treatment includes a multimodal protocol consisting of surgery, chemotherapy (doxorubicin and cisplatin), and hyperfractionated accelerated external beam radiotherapy (median patient survival of 10 months). For this reason, the identification of an effective systemic treatment for ATC would be a major advance in the management of this deadly thyroid cancer. The opportunity to test the sensitivity to different drugs of primary cells from ATC (pATC) cultures, obtained from each patients, could improve the effectiveness of the treatment. Then, the administration of inactive therapeutics could be avoided. Our aim is to investigate the antineoplastic effect of two tyrosine kinase inhibitors (TKIs; lenvatinib, vandetanib) in pATC obtained both from biopsy (biop-pATC), and from fine needle aspiration (FNA-pATC). The antiproliferative activity of lenvatinib and vandetanib was evaluated in 6 ATC patients, on biop-pATC, such as on FNA-pATC. A significant reduction of proliferation (obtained by WST-1 assay) versus control was shown with lenvatinib and vandetanib in FNA-pATC, as well as in biop-pATC. The percentage of apoptosis in FNA-pATC, or biop-pATC, increased with both compounds dose-dependently. pATC cells from FNA, or biopsy, had a similar sensitivity to lenvatinib and vandetanib. In conclusion, primary cells (biop-pATC or FNA-pATC) have a similar sensitivity to TKIs, and lenvatinib and vandetanib are effective in reducing cell growth, increasing apoptosis in ATC. The possibility to test the sensitivity to different TKIs in each patient could open the way to personalized treatments, avoiding the administration of ineffective, and potentially dangerous, drugs.